Blog jako narzędzie wspierające rozwój kompetencji dyskursywnej - Pędzisz, Joanna (Neofilolog, 2019)
The aim of the article is to present the ways in which blogs can be used in the teaching of German. The constant drive for making the teaching process more attractive and innovative encouraged teachers to search for innovative solutions in new media. Blogging may support the teaching process. The composition classes described below were based on selected blogs, whose content was supposed to encourage students to voice their opinions. Thus they had the opportunity to actively develop and improve their speaking and writing skills in the context of meaningful discourse.